Extending life by half [nuclear power plant relicensing]. - Amber, D.P (IEEE spectrum)
Licensed originally for just 40 years, one by one US nuclear power plants are qualifying for 20 more. So far 6 plants have had licenses renewed. The six were among the more than 40 percent of 103 operating US reactors whose licenses will expire before 2015, perhaps while they are still capable of efficient and safe production. Forty reactors may soon join the six; 14 have renewal applications in the review pipeline at the Nuclear Regulatory Commission (NRC) and the other 26 are expected to apply for renewal within the next six years. In all likelihood, most of the nuclear fleet will follow suit. The reasons for renewal are economic: the plants are almost paid for, and with construction out of the way, the costs of supplying electricity are finally competitive with those of other energy sources, such as coal and natural gas. But safety still concerns nuclear critics, troubled by the known and unknown hazards of aging. For example, cracks in the control rod mechanism, equipment at the heart of the reactor, were unforeseen and in fact previously thought not to exist. But they now seem a real aging problem after all, undermining confidence that more years of safe operation lie ahead